The impact of financial reform on private savings in Bangladesh - Abdur R. Chowdhury (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Over the course of the last decade, Bangladesh has implemented a broad-based program of financial and market reforms, encompassing changes in the structure of the financial system, prudential and supervisory frameworks, and monetary management. This paper estimates a savings function to evaluate the impact of various determinants of private savings in Bangladesh—with special emphasis on the impact of financial reform. The results show that the level of income, real interest rates, and the share of agriculture in GDP have a positive impact on the savings rate. Dependency rate and public savings rate, on the other hand, have a negative impact on private savings. Interestingly, the financial reform index has a negative impact on private savings. Hence reforms that were initiated since the late 1980s had actually reduced savings. An explanation for this result can be traced to the state of the banking sector beginning as early as 1972. Political interference dominated the selection of bank management and loan portfolios. Loans were extended to institutions and individuals with high credit risks leading to a high default rate. Moreover, the high proportion of effectively nonperforming assets also contributed to high interest margins and relatively low degree of financial intermediation. Despite a number of positive changes that have been introduced in the financial sector following reforms, these factors have adversely affected private savings in the economy. The pace of reform has not kept in line with the severity of the situation and further reforms in a timely fashion are necessary.
Keywords: O16; O53; E21; 330; private savings; financial reform; Bangladesh; time series analysis; Sparen; Kapitalmarktliberalisierung; Bankenpolitik; Bangladesch